HUBUNGAN POSISI MENERAN DENGAN LAMA KALA DUA PERSALINAN - Istiqamah; Khairul Anami; Iwan Yuwindry (LPPM Universitas Sari Mulia, 2023)
Background: The second stage of labor, also known as the expulsion stage, occurs when the baby's head stretches the vaginal tissues. The physiological process of the second stage of labor refers to a series of events that occur during this period, ending with the normal delivery of the baby. One aspect of respectful maternity care during labor is allowing the mother to choose her preferred pushing and birthing position. Allowing this choice can provide many benefits, including reduced pain and discomfort. Objective: To analyze the relationship between pushing position and the duration of the second stage of labor at TPMB Istiqamah Banjarmasin. Methods: This study used an analytical survey method with a cross-sectional approach. The sample consisted of 35 women in the second stage of labor at TPMB Istiqamah Banjarmasin. Results: The Chi-square test yielded a p-value of 0.005 (<0.05), indicating that the null hypothesis was rejected and the alternative hypothesis was accepted. This suggests a significant relationship between pushing position and the duration of the second stage of labor. The results showed that the lateral pushing position was more effective during the second stage of labor. Conclusion: There is a significant relationship between pushing position and the duration of the second stage of labor. The lateral pushing position was found to be more effective due to various factors that influence labor progression, including the passage, power, passenger, and labor position. Keywords: Second Stage of Labor, Laboring Mothers, Pushing Position